ACCOUNTING AND POLITICS: THE EFFECTS OF POLITICS ON THE ISSUANCE OF INTERNATIONAL ACCOUNTING STANDARDS – AN APPLIED STUDY IN THE IRAQI ENVIRONMENT (World Economics and Finance Bulletin, 2023)
Opinions differ on the relationship between accounting and politics. The first point of view says that accounting is abstract and accountants are professional people who are abstract from political issues and neutral, while the second point of view says that accounting is not abstract, and accountants cannot be abstracted from their social connections with members of society, including politicians and their concern as individuals in society, they have social interests and seek to maximize their economic benefit and through this pursuit they will participate in one way or another in the political process . The research includes a study of the opinions of a sample of Iraqi academics and professionals by analyzing a questionnaire form distributed to the selected sample with (94) forms and then using the (SPSS) software to prove the validity of the research hypotheses, so that the research ends with a number of important conclusions and recommendations including : that the society knowledge of the relationship between politics and accounting that the first uses the second for its purposes, and the second affects the first with its numbers, that accounting at the international level is politicized to serve certain parties, that the process of preparing accounting standards at the international level is witnessing various pressures, and that bias is practiced in that process to achieve economic interests
Keywords: Accounting; Politics; International accounting standards